Clinical and laboratory signs associated to serious dengue disease in hospitalized children - Sheila Moura Pone; Yara Hahr Marques Hökerberg; Raquel de Vasconcellos Carvalhaes de Oliveira; Regina Paiva Daumas; Tamiris Moura Pone; Marcos Vinicius da Silva Pone; Patricia Brasil (Brazilian Society of Pediatrics, 2016)
Objective: To evaluate the validity of clinical and laboratory signs to serious dengue disease in hospitalized children. Methods: Retrospective cohort of children (<18 years) hospitalized with dengue diagnosis (2007-2008). Serious dengue disease was defined as death or use of advanced life support therapy. Accuracy measures and area under the receiver operating characteristic curve were calculated. Results: Of the total (n = 145), 53.1% were female, 69% aged 2-11 years, and 15.9% evolved to the worse outcome. Lethargy had the best accuracy (positive likelihood ratio >19 and negative likelihood ratio <0.6). Pleural effusion and abdominal distension had higher sensitivity (82.6%). History of bleeding (epistaxis, gingival or gastrointestinal bleeding) and severe hemorrhage (pulmonary or gastrointestinal bleeding) in physical examination were more frequent in serious dengue disease (p < 0.01), but with poor accuracy (positive likelihood ratio = 1.89 and 3.89; negative likelihood ratio = 0.53 and 0.60, respectively). Serum albumin was lower in serious dengue forms (p < 0.01). Despite statistical significance (p < 0.05), both groups presented thrombocytopenia. Platelets count, hematocrit, and hemoglobin parameters had area under the curve <0.5. Conclusions: Lethargy, abdominal distension, pleural effusion, and hypoalbuminemia were the best clinical and laboratorial markers of serious dengue disease in hospitalized children, while bleeding, severe hemorrhage, hemoconcentration and thrombocytopenia did not reach adequate diagnostic accuracy. In pediatric referral hospitals, the absence of hemoconcentration does not imply absence of plasma leakage, particularly in children with previous fluid replacement. These findings may contribute to the clinical management of dengue in children at referral hospitals.